Capacity Enhancement for Aging Distribution Systems using Single Wire Earth Return - Wolfs, Peter; Hosseinzadeh, N.; Senini, S. (IEEE, 2007)
Single wire earth return systems, (SWER), are the low cost technology for rural power distribution and have global application. In the Australian setting, voltage regulation is becoming the determining factor for older SWER systems. In long systems, directly connected shunt reactors are used to compensate the effects of line to ground capacitance. The replacement of fixed shunt reactors with controllable reactors provides an opportunity to approximately double the capacity of an aging infrastructure. Three case studies based on the North Jericho system are presented and a range of practical implementation issues are discussed.